1996
DOI: 10.1016/s0304-3959(96)03177-6
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive responses to high and low rates of noxious cutaneous heating are mediated by different nociceptors in the rat: electrophysiological evidence

Abstract: Behavioral nociceptive responses evoked by relatively high rates of noxious radiant skin heating appear to be mediated by A delta nociceptor activation, whereas responses evoked by low rates of skin heating appear to be mediated by the activation of C-fiber nociceptors. This hypothesis was confirmed by the results of single unit recordings of A delta and C nociceptive afferent fibers isolated from the saphenous nerves of pentobarbital anesthetized rats. Heating the hind paw skin of the rat at a relatively high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(168 citation statements)
references
References 33 publications
8
159
1
Order By: Relevance
“…In our previous studies using adult female streptozotocin-diabetic rats, we have routinely found that thermal hypoalgesia develops in the hind paw after approximately 8 weeks [14,15,16,17] when using a system that selectively activates C fibres by increasing contact surface temperature from 30 to 50°C over a 20-second period [18]. Thermal hypoalgesia was prevented by treating rats with a neuroactive peptide that did not alter the general physiological condition of the animals [15,16], indicating that thermal hypoalgesia is unlikely to be a consequence of cachexia or altered thermal transduction properties of the skin.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies using adult female streptozotocin-diabetic rats, we have routinely found that thermal hypoalgesia develops in the hind paw after approximately 8 weeks [14,15,16,17] when using a system that selectively activates C fibres by increasing contact surface temperature from 30 to 50°C over a 20-second period [18]. Thermal hypoalgesia was prevented by treating rats with a neuroactive peptide that did not alter the general physiological condition of the animals [15,16], indicating that thermal hypoalgesia is unlikely to be a consequence of cachexia or altered thermal transduction properties of the skin.…”
Section: Methodsmentioning
confidence: 99%
“…From the present data we cannot conclude why IK 950 appeared more effective using mechanical stimulation, however, this difference could be explained by differences in the recruitment of primary afferent fiber types with thermal versus mechanical stimulation. While the slowly ramping heat stimulus selectively activates unmyelinated C fiber nociceptors (Yeomans and Proudfit, 1996), the von Frey filaments would have necessarily recruited both mechanosensitive Aδ and C nociceptors as well as low-threshold tactile Aβ fibers. Thus, the greater effect of IK 950 using mechanical compared to noxious thermal stimulation could have resulted from combined effects on multiple fiber types that culminated in a relatively greater reduction in primary afferent input converging on spinal nociceptive dorsal horn neurons.…”
Section: Effects Of Topical Sehis and Eets In An Lps Model Of Inflammmentioning
confidence: 99%
“…The potential significance of this issue led us to develop a noninvasive technique, as first described by Yeomans and colleagues (20), whereby we could reliably and reproducibly activate preferentially either C-or A/-nociceptors. Slow heating rates (2.5°C/s) applied to a hindpaw dorsum were used to activate capsaicin-sensitive heat nociceptors, and higher rates (7.5°C/s) of heating applied to the same cutaneous fields were used to activate a population of heat nociceptors that were capsaicin insensitive.…”
Section: Midbrain Circuitry That Distinguishes Between Escapable and mentioning
confidence: 99%